Competition for water resources experiences and management approaches in the US and Europe - Ziolkowska, Jadwiga R.; Peterson, Jeffrey M. (Waltham Elsevier, 2017)
Competition for Water Resources: Experiences and Management Approaches in the U.S. and Europe addresses the escalation of global issues regarding water scarcity and the necessary, cost-effective strategies that must be put in place in order to deal with escalating water crisis. The book evaluates use and competition for water resources in the U.S. and Europe, emphasizing the problems and challenges of dealing with tradeoffs in water. In addition, the book discusses water management strategies that can be used to optimize water use and allocation, mitigate water scarcity, and adapt to water scarcity. Supplementing the numerous case studies, the book includes lessons learned from applying specific strategies and approaches. This comprehensive overview and comparison of management practices across two continents is an invaluable resource for researchers, policymakers, and educators in water.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Water-supply -- United States; Water-supply -- Europe; Electronic books